SOPRANOTRONICS 101. AN ANALYTICAL APPROACH WITH REPERTORIAL PROPOSAL - BUHAICIUC, Mihaela (Studia Universitatis Babes-Bolyai Musica, 2023)
The current work aims to present an investigation of the past seventy years of Sopranotronics repertoire, approached through the eye of the performer. The Soprano Fach and the electronic environment merged in the last decades into a new interdisciplinary performance field, which is both artistic and scientific in its making. The Sopranotronics now offers a fresh vocal repertoire with challenging drama stories and thought-provoking art. Whether expressing a political disagreement (Nono’s La Fabbrica Illuminata) or describing a mythical story (Babbitt’s Philomel) in chamber works; writing a four-hour opera without dramatic action and a storyline (Glass’s Einstein on the Beach) or inventing the disembodied performance while the most humane character of the opera suffers because of this (Machover’s DATP) or chanting for spirits in an electro - acoustic aria (Crețu’s I.X.@100) and challenging any musical and vocal establishment in a dadaistic formula (Beldean’s Tekmirio) brings forward the human component of this experimental art worth performing.